Inoculation of maize seeds withPseudomonas putidaleads to enhanced seedling growth in combination with modified regulation of miRNAs and antioxidant enzymes - Aydinoglu, Fatma; Iltas, Omer; Akkaya, Ozlem (Springer, 2020)
Bacteria that positively interact with plant roots are defined as plant growth promoting rhizobacteria (PGPR). Although the positive effect of PGPR on plant growth has been widely studied, their impact on genetic regulation during plant growth processes remains largely unknown. Therefore, this study aimed to gain a deeper understanding of the regulatory role of miRNA and redox enzymes in response to PGPR at the maize seedling stage in leaf growth zone which consists of the meristem, elongation and mature zones. For this purpose, growth of the third leaf was monitored in response toPseudomonas putida(P. putida) KT2440 at phenotypic, physiological, cellular, kinematic, and transcriptional levels. This application resulted in an increase of 15% in shoot length, 56% in both shoot fresh/dry weight, 10% in chlorophyll amount, 8% in mature cell length, 15% in leaf elongation rate, and 7% in cell production; meanwhile final leaf length was unchanged, while leaf area and leaf width decreased by 22% and 16%, respectively. Ascorbate peroxidase and glutathione reductase activity increased throughout the leaf growth zone indicating a possible role in PGPR-plant interaction during transition between cell division, expansion and differentiation processes. The expression analysis of cell cycle check point marker genes revealed thatCycA2_1was mainly responsible for promoting cell proliferation in meristem. miR160, miR169 and miR408 were differentially expressed in the meristem, indicating their indirect regulatory roles in the cell division response to PGPR. In addition, miR160, miR319 and miR396 were downregulated in the elongation zone, which draws attention to their possible role in regulating cell elongation processes. In summary, cell cycle, redox and miRNA regulation in maize seedling growth zones in response toP. putidawere investigated for the first time in this study.
Keywords: Pseudomonas putida; Zea mays; PGPR; miRNAs; Plant-bacteria interaction; Cell cycle